Amaranth (Amaranthus hypochondriacus) Vicilin Subunit Structure - Quiroga, Alejandra Viviana (2010)
The 7S-globulin fraction is a minor component of the amaranth storage proteins. The present work provides new information about this protein. The amaranth 7S-globulin or vicilin presented a sedimentation coefficient of 8.6 ± 0.6 S and was composed of main subunits of 66, 52, 38, and 16 kDa. On the basis of mass spectrometry (MS) analysis of tryptic fragments, the 52, 38, and 16 kDa subunits presented sequence homology with sesame vicilin, whereas the 66 kDa subunit showed sequence similarity with a putative vicilin. Several characteristics of the 66 kDa subunit were similar to members of the convicilin family. Results support the hypothesis that the 7S-globulin molecules are composed of subunits coming from at least two gene families with primary products of 66 and 52 kDa, respectively. According to the present information, amaranth vicilin may be classified into the vicilin group that includes pea, broad bean, and sesame vicilins, among others.